2022
DOI: 10.1111/imj.15725
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pleural fluid cytology for the diagnosis of malignant pleural effusion: a retrospective cohort study

Abstract: BackgroundAs median survival time for patients with malignant pleural effusions (MPE) is nine months, rapid and accurate diagnosis is important. Cytological examination of pleural uid has a good speci city but imperfect sensitivity. Published estimates of sensitivity vary substantially and predictors of false negative cytology are not well established. We aim to establish a local estimate of pleural uid cytology sensitivity and identify risk factors for false negative cytology. MethodsWe conducted a retrospect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Considering the patient had persistent altered mental status with psychomotor retardation and bilateral non-pitting pedal edema, the TSH was checked, which was markedly elevated with low free T4 and T3 levels. A review of the literature revealed rare cases of pleural effusion in hypothyroidism, which were treated with timely hormonal replacement therapy [ 9 ]. Our patient had already been on oral levothyroxine since admission.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the patient had persistent altered mental status with psychomotor retardation and bilateral non-pitting pedal edema, the TSH was checked, which was markedly elevated with low free T4 and T3 levels. A review of the literature revealed rare cases of pleural effusion in hypothyroidism, which were treated with timely hormonal replacement therapy [ 9 ]. Our patient had already been on oral levothyroxine since admission.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrated a higher percentage of sensitivity than previous studies. 15 This method has been applied in many systems except for pleural effusions. 6,[16][17][18] To the Indian guidelines of 2020 and a recent paper by Shidham, among malignant effusions, cytology is helpful in determining the exact type, site, and stage of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Cytological evaluation is especially critical in patients with underlying malignancy as in our patient. The sensitivity of cytology for the diagnosis of B-cell lymphoma is between 42.8% and 94.5% [ 10 ]. Positive cytology may be associated with poor outcomes in patients with neoplastic pericardial disease.…”
Section: Discussionmentioning
confidence: 99%